Big Data Analytic, Big Step for Patient Management and Care in Puerto Rico - Borrero, Ernesto E. (Puerto Rico Health Sciences Journal, 2018)
This letter provides an overview of the application of big data in health care system to improve quality of care, including predictive modelling for risk and resource use, precision medicine and clinical decision support, quality of care and performance measurement, public health and research applications, among others. The author delineates the tremendous potential for big data analytics and discuss how it can be successfully implemented in clinical practice, as an important component of a learning health-care system.